Ultra-sensitive, sustainable, and selective electrochemical hydrazine detection by ALD-developed two-dimensional WO3 - Wei Zihan; Hai Zhenyin; Akbari M. K. Mohammad Karbalaei; Hu Jie; Hyde Lachlan; Verpoort F. V. K. Frensis Valter Kornelius; Zhuiykov S. Serge (2018, 2018)
Title screen